Quality Changes in Whale Shark (Rhiniodon typus Smith) Meat During Storage in Ice - K., Ashok Kumar; C.N., Ravishankar; R., Badonia; K.K., Solanki (Fishery Technology, 2025)
The biochemical, bacteriological and organoleptic changes in whale shark (Rhiniodon typus Smith) meat during storage in ice have been studied. There was a decrease in the proportion of soluble fractions of protein during storage. It was observed that the meat could be stored in ice up to 12 days in acceptable condition.